Contribution of Fishing Tour Boat Rental Business to Fisherman's Income in Rantau Baru Village, Pangkalan Kerinci Sub-District - Muhammad Zulfikri Firmansyah; Eni Yulinda; Tomi Ramadona (Berkala Perikanan Terubuk, 2023)
The research was conducted in Rantau Baru Village. The research was conducted to look at the existing conditions of the fishing boat rental business in Rantau Baru Village, the amount of working time for fishermen in the fishing tour boat rental business, and the contribution of the fishing tour boat rental business to fishermen's income in Rantau Baru Village, Pangkalan Kerinci District. The research method uses a survey method. Determination of respondents using the census method. The data collection method uses observation and interview methods with 35 fishermen in the fishing boat rental business. There were 3 informants who were determined purposively consisting of the surrounding community in the Rantau Baru village and employees at the Rantau Baru Village office. Fishing boat rental business consists of 3 types of boats namely diesel boat rental business, gasoline boat and rowing boat business. The amount of working time for fishermen in the fishing boat rental business in Rantau Baru Village consists of 3 businesses, namely the diesel engine boat rental business, which is 80 hours/month with a percentage of 31%. Gasoline engine boat rental business is 81 hours/month with a percentage of 30%. The rowboat rental business is 69 hours/month with a percentage of 27%. The rowboat rental business is IDR 2,208,167/month. The income contribution of fishermen from the fishing tour boat rental business, namely fishermen who own the diesel engine boat rental business, is IDR 634,175/month (21%). Fishermen who own a gasoline engine boat rental business, which is IDR 550,828/month (20%). and fishermen who own rowboat rental businesses is IDR 211,028/month (10%). The results of the calculation of the contribution of the fishing tour boat rental business show that the fishing tour boat rental business income has a small contribution to the income of fishermen in Rantau Baru Village.